Implementation of Good Corporate Governance in Supporting Financial Performance of Indonesian Islamic Banking Post Merger - Veni, Agata Valentina; Sucipto, Nurhadi; Sulistyowati, Wiwit Apit (Ilomata International Journal of Tax and Accounting, 2024)
PT BSI (PT Bank Sharia Indonesia) is one of the largest Islamic banks in Indonesia which is the result of the merger of three state-owned Islamic banks, including PT BNI Sharia, PT Bank Mandiri Sharia, and PT Bank BRI Sharia. This study aims to analyze the role of Good Corporate Governance in supporting the performance of Islamic Banking after the merger into BSI by analyzing the value of ROA and ROE before and after the merger, and reviewing the role of GCG in supporting financial performance as measured by the CGPI rating obtained from the company's annual report. This study uses a quantitative descriptive approach in analyzing differences in ROA and ROE before and after the merger, and analyzing the role of GCG in supporting this financial performance. The results of the analysis on GCG indicators show that there is no difference before and after the merger. Meanwhile, financial performance shows an increase compared to before the merger, which is indicated by the value of ROA and ROE in 2020 to 2022. This study gives insight in developing knowledge related to the financial performance after merger, and focusing on the sharia bank industry.